CHEMICAL ENGINEERING FOR THE PRODUCTION OF HALAL-CERTIFIED GELATIN ALTERNATIVES FROM PLANT-BASED SOURCES - Neneng Windayani; Michael Johnson; Sun Wei (Yayasan Adra Karima Hubbi, 2025)
The demand for halal-certified products is increasing globally, particularly in the food industry, where gelatin—a key ingredient in numerous products—often comes from animal sources, raising concerns for halal dietary compliance. This research focuses on developing plant-based alternatives to gelatin, specifically designed to meet halal certification standards. The primary objective of this study is to explore the chemical engineering processes involved in producing gelatin alternatives from plant-based sources, ensuring they meet the physical, chemical, and sensory properties required for food applications. Using a combination of plant-based polysaccharides, such as agar, carrageenan, and pectin, this study employs extraction, hydrolysis, and gelling techniques to develop suitable alternatives. The research utilizes a systematic approach, including experimental trials, chemical analyses, and sensory evaluations, to assess the functional and sensory qualities of the plant-based gelatin alternatives. Results indicate that certain plant-derived alternatives exhibit comparable gelling, stability, and texture to traditional gelatin, while also adhering to halal certification requirements. The study concludes that plant-based gelatin alternatives offer a promising, sustainable solution for the halal food industry, with potential applications in a wide range of products such as confectionery, dairy, and pharmaceuticals. These findings provide valuable insights into the development of halal-compliant, plant-based food ingredients, contributing to both innovation and sustainability in the food industry.